RESISTANCE TRAINING IN OLDER HIPERTENSIVE (Fiep Bulletin - online, 2014)
This research is a study of bibliographical revision subsidized by scientific articles, aims to observe the importance of resistance training for the elderly with hypertension, because high blood pressure is one of the diseases that most affect the Brazilian population and that has as main characteristic the high blood pressure, reaching people from all age ranges, adults, young and mostly elderly, people of both sexes and which wants to race, this research had emphasis on studies of the year 2008 to 2013, however, according to the criteria for inclusion and exclusion of studies were not found in the years 2010 and 2013, 8 were selected studies, 4 in the year 2008, 1 in the year 2009, the year 2011 1 and 2 in the year 2012, That showed reductions in the values of blood pressure in elderly people, therefore, it can be concluded that the resistance training is important in the life of elderly hypertensive patients, therefore, can be a way of preventing Hypertension and even a form of non-pharmacological treatment.
Keywords: Arterial hypertension; resistance training; elderly